Productivity and Impact of the Scientific Production on Human-Computer Interaction in Scopus from 2018 to 2022 - Gonzalez-Argote, Javier; Castillo-González, William (Multidisciplinar (Montevideo), 2023)
Introduction: Bibliometrics plays a crucial role in scientific research by providing valuable insights and guiding future research endeavors.Objective: To assess the productivity and impact of the worldwide scientific production on HCI in Scopus (2018-2022).Method: A descriptive observational bibliometric study of scientific production on HCI in Scopus (2018-2022) was conducted. A population of 178,914 documents in the “Human-Computer Interaction” research area was identified using SciVal. All data were extracted from SciVal. IBM SPSS Statistics 27 was used to determine Pearson's correlation coefficients, with statistical significance for p < 0.05.Results: The number of documents (Ndoc) and field-weighted citation impact (FWCI) showed a quantitative increase during the period studied. The highest Ncit corresponded to the oldest documents. Conference papers and articles were the main types of documents. ACM International Conference Proceeding Series led the list of sources in both Ndoc and Ncit. The highest FWCI corresponded to Computers in Human Behavior. A positive and statistically significant correlation (r = 0.494, p < 0.001) was found between the authors’ Ndoc and Ncit and between the countries’ Ndoc and Ncit (r = 0.967, p < 0.001). China was the most productive country while the United States led in terms of Ncit and FWCI. International collaboration was the most common type of collaboration.Conclusions: The examination of the scientific production revealed a trend characterized by quantitative expansion. This, coupled with impact indicators reliant on citations, substantiates the prominence of the investigated research domain